ANALISIS FAKTOR–FAKTOR PENYEBAB RENDAHNYA KEAKTIFAN PESERTA DIDIK DALAM PROSES PEMBELAJARAN MATA PELAJARAN IPA - Dinata, Serica; Aulia Dinata, Serica Aulia Dinata; Saputra, Deka; Ismawanti4, Afifah Nur (Jurnal Tunas Pendidikan, 2024)
Learning natural science subjects is an integral part of the educational curriculum which aims to develop students' understanding and skills in various scientific concepts. However, the low level of student activity in the science learning process is a challenge that needs to be addressed seriously. This research aims to analyze the factors causing the low level of student activity in the learning process of science subjects. This research method uses a qualitative approach with data collection techniques in the form of observation, interviews and document analysis. Research participants consisted of science teachers and class students who were selected purposively. Data were analyzed using thematic analysis techniques. The research results show that there are several factors that cause low student activity in learning science. These factors include a lack of student involvement in the learning process, unattractive teaching methods, lack of adequate learning facilities and resources, as well as students' motivation and interest in science subjects. The implication of this research is the need for more attention from educators to increase students' activeness in science learning. This can be done through developing innovative learning methods, providing adequate facilities, as well as efforts to increase students' motivation and interest in science subjects. In this way, it is hoped that students' activeness in the science learning process can be increased significantly, so that learning objectives can be achieved more optimally.